Construction of anisotropic nanostructures by self-assembly of aggregation-induced emission driven from tris-branched [2]rotaxane based molecular zipper. (June 2022) - Arumugaperumal, R.; Alene, D.Y.; Shellaiah, M.; Srinivasadesikan, V.; Awasthi, K.; Sun, K.W.; Lin, M.-C.; Ohta, N.; Chung, W.-S.
Abstract: The rotaxane-based molecular machines can lead to the appearance of unconventional operations and properties thus, by integrating with aggregation-induced emission (AIE) features to control the construction of polymorphism through supramolecular self-assembly can reach an amazing level of intelligent materials. We rationally described a tris-branched TPE [2]rotaxane RZ 3+ of a molecule shuttle, composed of t -butylcalix [4]arene macrocycle, a single axle incorporating ammonium motif, and a bifurcated double strand each containing 1, 2, 3-triazolium (Tz) cationic unit that terminated with a tetraphenylethene (TPE) stopper. The "concealed" and "exposed" state of the ammonium moiety by a [2]rotaxane RZ 3+ is displayed to correspond to opening and closing of the double strand, respectively, which resembles a zipper-like functioning. Distinctive anisotropic nanostructures including nanofibers, nanorods, coarsely truncated shapes, pseudocubes, nanocubes and so on can be forthrightly fabricated by fine tuning the solvent polarity and or the shuttling movement of the macrocycle in THF/water mixture to manipulate the self-assembly processes. Self-assembly reveals that nanocubes can only be constructed by TB 3+ and RZ 3+ molecules in aqueous media but not by RZ + and RZ 2+ under similar conditions. The fascinating nanocubes was mainly controlled precisely by two major factors i.e., Tz cationic units and aqueous medium. It is worth mentioning that, exotic shape organic nanocubes were seldomly reported in rotaxane-based nano-objects owing to unfavorable thermodynamics for nanocubes formation. This study highlights the benefits of using Tz cationic units, which not only serve as secondary molecular station but also control the self-assembly process to form nanocubes in aqueous medium, providing a new avenue for nanomaterials technology and further enriching the applications of mechanically interlocked molecules (MIMs). Graphical abstract: The AIE-active [2]rotaxane RZ 3+ molecular shuttle, operating like a zipper functioning, could be driven by the addition of acid/base stimuli sequentially. Controllable anisotropic nanostructures could be constructed by simply switching the water fraction ( f w ) and or the shuttling movement of the macrocycle in THF/water mixture overwhelmingly induced the arrangement of building blocks through the synergistic effects. Image 1 Highlights: Tris-branched TPE [2]rotaxane derivatives were synthesized through threading-end-capping protocol using click chemistry. Displays a mechanical motion reminiscent of zippering that can be driven by acid/base stimuli. Nanostructures can be fabricated by tuning the solvent polarity and or the shuttling movement of the macrocycle in THF/water. Nanocubes were mainly controlled precisely by two major factors i.e., Tz cationic units and aqueous medium. Tz cationic units act as molecular stations and control the self-assembly process to form nanocubes in aqueous medium.